Open vs. Closed Skill Sports and the Modulation of Inhibitory Control - Wang, Chun-Hao; Chang, Che-Chien; Liang, Yen-Ming; Shih, Chun-Ming; Chiu, Wen-Sheng; Tseng, Philip; Hung, Daisy L.; Tzeng, Ovid J. L.; Muggleton, Neil G.; Juan, Chi-Hung (PLOS ONE, 2013)
Background Inhibitory control, or the ability to suppress planned but inappropriate prepotent actions in the current environment, plays an important role in the control of human performance. Evidence from empirical studies utilizing a sport-specific design has shown that athletes have superior inhibitory control. However, less is known about whether this superiority might (1) still be seen in a general cognitive task without a sport-related context; (2) be modulated differentially by different sporting expertise (e.g., tennis versus swimming). Methodology/Principal Findings Here we compared inhibitory control across tennis players, swimmers and sedentary non-athletic controls using a stop-signal task without a sport-specific design. Our primary finding showed that tennis players had shorter stop-signal reaction times (SSRTs) when compared to swimmers and sedentary controls, whereas no difference was found between swimmers and sedentary controls. Importantly, this effect was further confirmed after considering potential confounding factors (e.g., BMI, training experience, estimated levels of physical activity and VO2max), indicative of better ability to inhibit unrequired responses in tennis players. Conclusions/Significance This suggests that fundamental inhibitory control in athletes can benefit from open skill training. Sport with both physical and cognitive demands may provide a potential clinical intervention for those who have difficulties in inhibitory control.